Modeling Bioavailability Limitations of Atrazine Degradation in Soils - Chavez Rodriguez, Luciana; Ingalls, Brian; Meierdierks, Jana; Kundu, Kankana; Streck, Thilo; Pagel, Holger (Frontiers in Environmental Science, 2021)
Pesticide persistence in soils is a widespread environmental concern in agro-ecosystems. One particularly persistent pesticide is atrazine, which continues to be found in soils and groundwater in the EU despite having been banned since 2004. A range of physical and biological barriers, such as sorption and mass-transfer into bacterial cells, might limit atrazine degradation in soils. These effects have been observed in experiments and models working with simplified systems. We build on that work by developing a biogeochemical model of the degradation process. We extended existing engineered system models by including refined representations of mass-transfer processes across the cell membrane as well as thermodynamic growth constraints. We estimated model parameters by calibration with data on atrazine degradation, metabolite (hydroxyatrazine) formation, biomass, and isotope fractionation from a set of controlled retentostat/chemostat experiments. We then produced site-specific model predictions for arable topsoil and compared them with field observations of residual atrazine concentrations. We found that the model overestimated long-term atrazine biodegradation in soils, indicating that this process is likely not limited by bioavailability or energetic constraints of microbial growth. However, energetic constraints of microbial growth, together with sorption-limited bioavailability, could explain the long-term fate and persistence of the main degradation metabolite hydroxyatrazine. Future studies should seek alternative controls that drive the observed atrazine persistence in soil. This work helps to bridge the gap between engineered and natural systems, allowing us to use laboratory setups to gain insight into real environmental systems.